Some Identities of the Modified Jacobsthal and Modified Jacobsthal – Lucas Numbers by the Matrix Method - Tatong, Mongkol (Burapha Science Journal, 2026)
In this paper, we study the modified Jacobsthal and modified Jacobsthal – Lucas numbers, and we define the 2 x 2 matrices , , , which satisfy the relation , , and . Moreover, we prove some identities of modified Jacobsthal and modified Jacobsthal – Lucas numbers, some of the relation between modified Jacobsthal and modified Jacobsthal – Lucas numbers, and some sum formulas for modified Jacobsthal and modified Jacobsthal – Lucas numbers by using these matrices. In this paper, we study the modified Jacobsthal and modified Jacobsthal – Lucas numbers, and we define the 2 x 2 matrices , , , which satisfy the relation , , and . Moreover, we prove some identities of modified Jacobsthal and modified Jacobsthal – Lucas numbers, some of the relation between modified Jacobsthal and modified Jacobsthal – Lucas numbers, and some sum formulas for modified Jacobsthal and modified Jacobsthal – Lucas numbers by using these matrices.